2021
DOI: 10.1186/s13041-021-00777-8
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate reduces starvation-induced ER stress by inhibiting ER-phagy in hypothalamic cells

Abstract: Palmitate is a saturated fatty acid that is well known to induce endoplasmic reticulum (ER) stress and autophagy. A high-fat diet increases the palmitate level in the hypothalamus, the main region of the brain regulating energy metabolism. Interestingly, hypothalamic palmitate level is also increased under starvation, urging the study to distinguish the effects of elevated hypothalamic palmitate level under different nutrient conditions. Herein, we show that ER-phagy (ER-targeted selective autophagy) is requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Regarding other types of autophagy that could be affected by TFEB activation, the flux of autophagy or ER-phagy was not increased by HFD feeding despite TFEB activation in pancreatic islets 70 . These results are consistent with previous papers reporting no increase in autophagy or ER-phagy flux by PA or HFD feeding 77 , 91 , 92 and could be attributable to distinct molecular machinery that is required for the autophagic removal of different organelles.…”
Section: Functional Role Of Tfeb-mediated Mitophagy Under Conditions ...supporting
confidence: 93%
“…Regarding other types of autophagy that could be affected by TFEB activation, the flux of autophagy or ER-phagy was not increased by HFD feeding despite TFEB activation in pancreatic islets 70 . These results are consistent with previous papers reporting no increase in autophagy or ER-phagy flux by PA or HFD feeding 77 , 91 , 92 and could be attributable to distinct molecular machinery that is required for the autophagic removal of different organelles.…”
Section: Functional Role Of Tfeb-mediated Mitophagy Under Conditions ...supporting
confidence: 93%
“…Liu and colleagues found that Dexmedetomidine induces ER-phagy by activating FAM134B, which subsequently attenuated the ER stress (75). Globular adiponectin has been found to activate SEC62mediated ER-phagy, thus mitigating ER stress-induced cardiomyocytes apoptosis (76).However, Lim et al found that palmitate reduces ER stress by inhibiting ER-phagy (77). Persistent ER stress has been demonstrated to cause apoptosis of alveolar epithelial cells, whereas appropriate ER-phagy decreases apoptosis by alleviating ER stress.…”
Section: Er-phagy Inhibits the Apoptosis Of Alveolar Epithelial Cells...mentioning
confidence: 99%